Criminal Liability of Perpetrators of Extortion Crimes Using Escort and Security Services as a Mode for Container Trailer Truck Transport Fleets (Study of Decision No. 952/PID.B/2021/PN.JKT.UTR) - Johansen E.H.Hasugian; Martono Anggusti; Lesson Sihotang (Journal of Legal and Cultural Analytics, 2025)
The phenomenon of crime occurs every day and is experienced by Indonesian society, such as mugging, armed robbery, theft, robbery, assault, rape, murder, and youth brawls, which are known as street crimes. One of the cases that often occurs is extortion. The crime of extortion can occur anywhere and anytime, harming the victim and society. Therefore, extortion perpetrators are given severe sentences to provide a deterrent effect. Extortion is an act that aims to benefit oneself by using violence or threats so that the victim gives something. This crime violates legal norms and has a detrimental impact on the victim, so it requires legal resolution. This study uses a normative legal method with a statute approach, a fact approach, and a case approach. Based on Decision No. 952/Pid.B/2021/PN Jkt.Utr, the judge determined extortion as a crime that meets the objective and subjective elements in Article 368 of the Criminal Code. Further analysis is needed to understand the judge's considerations and the application of the principle of justice in the decision.